Pemilihan Daerah Pelayanan Sampah di Bandung Utara Berdasarkan Parameter Daerah Prioritas SNI-19-2454-2002 - Lutfi Adhari; Yulianti Pratama; Nico Halomoan (Fakultas Teknik, 2020)
The North Bandung Service Area (WP) is a waste WP which has a service level in 2017 of 79.5%, there are still some unserved areas. Each North Bandung WP has different regional characteristics, so according to previous research, service areas were formed using the cluster analysis method to classify regions based on regional characteristics in order to support the target service level of 90%. The purpose of this planning is for the development of previous research by planning the existing priority service area waste management system as an effort to achieve the target of waste services in WP North Bandung. The selection of priority areas is based on the parameters for determining priority areas for SNI 19-2454-2002. This research is expected to solve the problem of waste management system in WP North Bandung.